Subjective memory complaints predict baseline but not future cognitive function over three years: results from the Western Australia Memory Study. (2nd October 2018) - Sohrabi, Hamid R.; Weinborn, Michael; Laske, Christoph; Bates, Kristyn A.; Christensen, Daniel; Taddei, Kevin; Rainey-Smith, Stephanie R.; Brown, Belinda M.; Gardener, Samantha L.; Laws, Simon M.; Martins, Georgia; Burnham, Samantha C.; et al.
ABSTRACT: Background: This study investigated the characteristics of subjective memory complaints (SMCs) and their association with current and future cognitive functions. Methods: A cohort of 209 community-dwelling individuals without dementia aged 47–90 years old was recruited for this 3-year study. Participants underwent neuropsychological and clinical assessments annually. Participants were divided into SMCs and non-memory complainers (NMCs) using a single question at baseline and a memory complaints questionnaire following baseline, to evaluate differential patterns of complaints. In addition, comprehensive assessment of memory complaints was undertaken to evaluate whether severity and consistency of complaints differentially predicted cognitive function. Results: SMC and NMC individuals were significantly different on various features of SMCs. Greater overall severity (but not consistency) of complaints was significantly associated with current and future cognitive functioning. Conclusions: SMC individuals present distinctive features of memory complaints as compared to NMCs. Further, the severity of complaints was a significant predictor of future cognition. However, SMC did not significantly predict change over time in this sample. These findings warrant further research into the specific features of SMCs that may portend subsequent neuropathological and cognitive changes when screening individuals at increased future risk of dementia.